Why didn't the progressive wave pave the way for a better world? - Barbosa dos Santos, Fabio Luis (2021)
In a context of worsening economic and social problems in the face of the pandemic, where a Keynesian revival is being observed in industrialized countries, this article questions whether it makes sense to revive progressivism as a civilizing alternative for Latin America. The text adresses this issue through the following steps. Initially, the ideology of progress is problematized. Then an overview of the situation of different Latin American countries in the context that preceded the outbreak of the Conavirus pandemic is undertaken, to explore the hypothesis of the exhaustion of progressivism. Contrary to explaining the current political moment as a reaction to past governments, it is suggested that the Pink Tide attempt to contain a historical process of de-socialization within the framework of the structural crisis of capitalism, implied the use of practices, devices and policies that ended up accelerating this same process, which is further detailed in the Brazilian case.  The notions of "accelerationist containment," "regressive progressivism," and "inclusive neoliberalism" are the proposed keys to examining the contradictions of progressivism and understanding why the Pink Tide has not paved the way for a better world. The text is closed by a parallel between the expectations of a Keynesian return in the context of the pandemic, and the limits of the progressive landscape to face the structural problems that this unforeseen situation aggravates.